Process Optimization and Physicochemical Characteristics Analysis of Soluble Dietary Fiber from Corn Bran Modified by Composite Enzymes - Xuyao WEI; Caixia JIANG; Xiangrui ZENG; Meng WANG; Xiqun ZHENG; Xiaolan LIU (Shipin gongye ke-ji, 2024)
To investigate the optimal extraction process and functional characteristics of soluble dietary fiber (SDF) from corn bran. This study used corn bran, a by-product of corn processing, as raw material to extract soluble dietary fiber from corn bran through composite enzyme modification. The optimal process parameters were determined through single factor experiments and response surface methodology optimization, and their physicochemical properties were studied. The results showed that the extraction yield of SDF reached the highest value of 16.64%±0.21% when the content of cellulase was 1.5%, the content of xylanase was 1%, the enzymolysis temperature was 55 ℃ and enzymolysis time was 150 min. Its solubility was 87.63%±0.43%, the holding water capacity was 2.87±0.16 g/g, the oil holding capacity was 2.30±0.12 g/g, the glucose adsorption capacity was 5.32±0.12 mmol/g. Under simulated stomach (pH2.0) and intestinal environment (pH7.0), cholesterol adsorption capacity was 11.74±0.15 and 42.93±0.08 mg/g and sodium cholacte adsorption capacity was 15.43±0.17 and 50.67±0.10 mg/g, respectively. The research results can provide theoretical reference for the development and utilization of soluble dietary fiber from corn bran.